Legitimacy and the European Union : the contested polity - Banchoff, Thomas F., 1964-; Smith, Mitchell P., 1960- (Routledge, 1999)
Beetham and Lord provide concise and analytical coverage of a key topic within the European Union, that is, the legitimacy of European supra-national governance.
Keywords: European Union.; European Union; Union européenne.; European federation.; Legitimacy of governments -- Europe.; Légitimité des gouvernements -- Europe.; Construction européenne.; LAW -- International.; European federation; Legitimacy of governments; Europe; Competence.; Legitimacy.; Democracy.; Political parties.; European integration.; Community law.; Partis politiques et Union européenne.; Europe de l'Ouest -- Unité.